(untitled) (8gen-ART, 2022)
The aim of this research is to analyze the movie named Passengers, in which the events between two space travelers are told and a humanoid robot is partially included in the story, in terms of fictional space. For this reason, Avalon, the main location of the movie, has been examined in terms of the design criteria of fictional spaces. According to the scenario, the movie takes place in the spacecraft called Avalon, which goes to space with its 5000 colonists and 258 crew to establish a colony on Homestad II, the fourth planet conquered by mankind. The movie mentioned within the scope of the research is watched and evaluated within the scope of the main subject. Within the scope of the Fear and Space elective course given at Kütahya Dumlupınar University, Faculty of Architecture, Department of Interior Architecture, the students also watched the aforementioned movie and submitted various optional opinions and suggestions about the movie in the weekly course evaluation form. These forms were also used within the scope of the research.